Insulin‐like Growth Factor‐1 Impacts p53 Target Gene Induction in UVB‐irradiated Keratinocytes and Human Skin. (1st June 2020) - Alkawar, Abdulrahman M.M.; Castellanos, Amber J.; Carpenter, Mae Alexandra; Hutcherson, Rebekah J.; Madkhali, Mariyyah A.O.; Johnson, Ron Michael; Bottomley, Michael; Kemp, Michael G.
Abstract: The tumor suppressor protein p53 limits mutagenesis in response to ultraviolet‐B (UVB) light exposure by activating the transcription of genes that mitigate the damaging effects of UVB radiation on DNA. Because most nonmelanoma skin cancers (NMSCs) occur in older individuals, it is important to understand the process of mutagenesis in the geriatric skin microenvironment. Based on previous studies demonstrating that geriatric skin expresses lower levels of the growth factor insulin‐like growth factor‐1 (IGF‐1) than young adult skin, a role for IGF‐1 in the regulation of p53 target genes was investigated in both human keratinocytes in vitro and human skin explants ex vivo. The products of the p53 target genes p21 and DNA polymerase eta (pol η) were found to be increased by UVB exposure in both experimental systems, and this induction was observed to be partially abrogated by depriving keratinocytes of IGF‐1 in vitro or by the treatment of keratinocytes in vitro and human skin explants with an IGF‐1 receptor antagonist. Because p21 and pol η function to limit mutagenic DNA replication following UVB exposure, these results suggest that NMSC risk in geriatric populations may be due to age‐dependent decreases in IGF‐1 signaling that disrupt p53 function in the skin. Abstract : UVB light exposure leads the tumor suppressor protein p53 to up‐regulate the expression of gene products that limit the likelihood of mutagenic DNA synthesis in epidermal keratinocytes in the skin. Geriatric individuals are prone to developing skin cancers and are known to express reduced levels of IGF‐1 in the skin. Here, we show that reduced IGF‐1 signaling in keratinocytes in vitro and skin explants ex vivo results in a failure to properly induce the expression of several antimutagenesis proteins after UVB irradiation, including the cell cycle checkpoint protein p21 and the translesion DNA polymerase Pol eta.